Low-mineral direct drinking water in school may retard height growth and increase dental caries in schoolchildren in China. (June 2018) - Huang, Yujing; Wang, Jia; Tan, Yao; Wang, Lingqiao; Lin, Hui; Lan, Lan; Xiong, Yu; Huang, Wei; Shu, Weiqun
Abstract: Although direct drinking water (DDW) systems that utilize a reverse-osmosis technique are thought to be harmful to children's development by reducing their daily mineral intake, few population data are available regarding this topic. We conducted an eco-epidemiological study to investigate the influence of low-mineral DDW on the development of schoolchildren. We collected developmental parameters of 13, 723 girls and 16, 161 boys before and after the introduction of DDW systems in 25 schools and measured the mineral levels in the DDW of each school. The DDW in 22 schools had lower-than-recommended levels of magnesium and calcium (magnesium, 10 mg/L and calcium, 20 mg/L, WHO). We found that children exposed to low-mineral DDW exhibited reduced height and diminished height increases as well as higher prevalences and incidences of hypoevolutism and dental caries ( p  < 0.01). This exposure was a risk factor for a greater incidence of both hypoevolutism and dental caries in children (RR = 7.110 (1.688, 29.953) and 1.813 (1.309, 2.509), respectively; p  < 0.01). Our results suggest that low-mineral DDW may retard height growth and promote the incidence of dental caries in schoolchildren; thus, schools should choose DDW treatment systems that retain the minerals in water. Highlights: Children drunk low-mineral direct drinking waterin school had lower height and height increases. Children drunk low-mineral direct drinking waterin school had higher prevalence and incidence of hypoevolutism. Drinking low-mineral direct drinking water inschool was positively associated with the incidence of hypoevolutism. Children drunk low-mineral direct drinking waterin school had higher prevalence and incidence of dental caries. Drinking low-mineral direct drinking water inschool was positively associated with the incidence of dental caries. Drinking low-mineral direct drinking water inschool was positively associated with the incidence of dental caries.